In situ determination of 137Cs inventory in soil using a field-portable scintillation gamma spectrometer-dosimeter. (May 2021) - Ramzaev, V.; Bernhardsson, C.; Dvornik, A.; Barkovsky, A.; Vodovatov, A.; Jönsson, M.
Abstract: A new empirical method for in situ determination of the inventory of 137 Cs in soil ( A Cs, kBq m −2 ) at grasslands and forests using a field-portable NaI(Tl) scintillation spectrometer-dosimeter was developed. The method is based on evaluation of the ambient dose equivalent build-up factor. The practical implementation of the new method with the spectrometer-dosimeter does not require a priori knowledge of the vertical distribution of 137 Cs in soil. Moreover, the method allows assessing a value of the mean migration depth of 137 Cs in soil ( Z ) in terms of g cm −2 . The 95% confidence interval for the mean value of the conversion coefficients from the ambient dose equivalent build-up factor to A Cs and to Z is less than 10%. The new method has been developed and verified using published data that where obtained at territories in Russia and Belarus heavily contaminated with 137 Cs ( A Cs  > 37 kBq m −2 ) due to the Chernobyl accident. Therefore, the survey of less contaminated areas requires additional validation of this method. Highlights: A novel method for in situ determination of 137 Cs inventory in soil was developed. The method is based on using the ambient dose equivalent build-up factor. The method can be applied for the in situ measurements in open field and in forest. The method has been verified at heavily contaminated areas in Russia and Belarus.